2004
DOI: 10.1080/0963928042000306828
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging a deep approach to learning through curriculum design

Abstract: Accounting educators are concerned by research suggesting that accounting students frequently adopt a surface approach to learning given that this approach has been shown to result in undesirable learning outcomes (Eley, 1992; Booth et al., 1999). Despite mixed empirical evidence, the possibility of encouraging students to adopt a deep approach to learning through interventions in the learning context is suggested by the approaches to learning and metacognition literatures. Functional Linguistics (Halliday, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
2
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 24 publications
4
82
2
7
Order By: Relevance
“…Previous research in the accounting education literature found it difficult to support change by accounting students from surface to deep learning (English et al, 2004;Hall et al, 2004;Ballantine et al, 2008;Fox et al, 2010). These studies involved limited interventions to support deep learning with apparently many aspects of the design and delivery of the courses involving traditional approaches that could be seen as supporting surface learning (Boyce et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in the accounting education literature found it difficult to support change by accounting students from surface to deep learning (English et al, 2004;Hall et al, 2004;Ballantine et al, 2008;Fox et al, 2010). These studies involved limited interventions to support deep learning with apparently many aspects of the design and delivery of the courses involving traditional approaches that could be seen as supporting surface learning (Boyce et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has found supporting deep learning to be a challenging issue for accounting students (English et al, 2004;Hall et al, 2004;Ballantine et al, 2008;Fox et al, 2010); and also for students in a range of other disciplines including, for example, education, science, psychology, nursing and medicine (Baeten et al, 2010). Also, these previous studies did not include interventions designed to support students to experience three preconditions for them to experience deep learning: high-level relevance structures, high-level conceptions of learning and intrinsic motivation.…”
Section: This Study Has Addressed the Following Research Questionmentioning
confidence: 99%
“…En nuestra opinión, con este material se beneficia a aquellos alumnos cuyo estilo de aprendizaje dominante (según el modelo de Felder y Silverman, 1988) es activo (frente a reflexivo), sensitivo (frente a intuitivo), visual (frente a auditivo) y secuencial (frente a global), y que pueden encontrar dificultades extra para superar la materia empleando sólo materiales más tradicionales (clase expositiva). Además, hay numerosos estudios que consideran que los estudiantes que siguen metodologías basadas en el aprendizaje autónomo tienen un estilo de aprendizaje menos superficial, más profundo, reflexivo, autodirigido y versátil, en comparación con los que utilizan métodos tradicionales (Baker et al, 2007;Lycke et al, 2006;Tiwari et al, 2006), y que este enfoque de aprendizaje profundo suele ser un buen predictor de éxito académico, mientras que un enfoque superficial suele asociarse a peores resultados (English et al, 2004;Snelgrove, 2004;Snelgrove y Slater, 2003).…”
Section: Resultados Y Discusiónunclassified
“…Así, son muchas las investigaciones que establecen que el enfoque profundo es un buen predictor del éxito académico y el enfoque superficial de peores resultados Diseth y Martinsen, 2003;English, Luckett y Mladenovic, 2004;Núñez et al, 2000;Phan, 2006;Ruiz-Lara, Hernández-Pina y Ureña, 2008;Snelgrove, 2004;Rodríguez, 2005;Snelgrove y Slater, 2003;Valle et al, 2000). Por el contrario, autores como Valle et al (1999), Bacon (2004), Edward (2004) y Groves (2005) no encuentran relaciones directas entre enfoques de aprendizaje y resultados académicos, o no siempre se producen.…”
Section: Relación De Los Enfoques De Aprendizaje Con Variables Del Counclassified